Pharmacopoeia roles and responses: A systemic resilience approach to COVID-19 pandemic - Shruti Rastogi; Surendra Kumar Sharma; Jaishiv Chauhan; Pawan Kumar Saini; Robin Kumar; Rajeev Singh Raghuvanshi; Gaurav Pratap Singh Jadaun (Elsevier, 2022)
The Coronavirus Disease (COVID-19) is sweeping around the world at a rapid pace resulting in severe health crises across the globe. The pandemic condition has forced the government, regulatory authorities, bio/pharmaceutical industry, and healthcare system to take novel measures to address the crisis. The race for development of medicines and vaccines for treatment of COVID-19 is well under way and regulatory authorities are making efforts to safely deliver it into hands of public. As ever, pharmacopoeias played an active role in providing a framework of standards for the development, manufacturing, and quality of life-saving COVID-19 related medicines. The COVID-19 crisis has compelled the pharmacopoeias to redefine their role and show unprecedented levels of flexibility in extending their services to the stakeholders, developing new drug standards, and simultaneously ensuring the safety of their staff. During this pandemic, pharmacopoeias operated in a triangular chain system with regulators and pharmaceutical manufacturers to evaluate potential products for treatment of COVID-19. The present article provides an insight on the roles, challenges, and responses of the pharmacopoeias to deal with the current situation due to COVID-19 and emphasizes on new opportunities for collaborations to set standards for COVID-19 related drugs.